Autumn protogyny and spring protandry: Mechanisms and adaptive significance in a Japanese headwater frog, Rana sakuraii - Tokio Miwa (PLoS ONE, 2025)
In temperate-zone vertebrates, almost all studies on protandry and protogyny are based on spring breeding migrations or breeding sites and are discussed in terms of the advantages for pairing. However, both autumn migrations and wintering conditions are also important for studies on these behaviors because, in some vertebrates, pairings occur at wintering sites before the emergence at the main breeding sites. Nevertheless, the significance of both autumn migrations and wintering conditions for pairing is scarcely recognized or studied. This study is the first to report on the mechanism and adaptive significance of “autumn protogyny and spring protandry” in a temperate-zone amphibian species. I investigated the annual migrations of Rana sakuraii, a Japanese early spring breeding (ESB) frog species, for over 21 years. This species migrates toward its breeding sites during autumn, hibernates either at the same breeding sites or close by, and breeds immediately upon emergence from hibernation. Protogynous autumn migrations and protandrous ESB migrations were clearly observed every year, depending on the same factor: the difference in threshold temperature for hibernation (which was higher for females than males). Frogs hibernated in groups under boulders in streams. Pairings began during autumn migrations and mostly ended during the aquatic hibernation period. Based on the results of this study and other related reports, I propose the hypothesis that temperate-zone ESB amphibians exhibit “autumn protogyny and spring protandry,” which are not independent and always occur together successively. Moreover, to explain the adaptive significance of these contrasting behaviors, I propose “the surefire pairing hypothesis”: these pairings occur more securely in two stages, before and after emergence at main breeding sites (i.e., “Early pairings” and “Normal pairings”). Such pairing advantages are provided by autumn protogyny and group hibernation for “Early pairings,” and by spring protandry for “Normal pairings.”.